Correction: Key role of surface oxidation and reduction processes in the coarsening of Pt nanoparticles. Issue 45 (16th November 2017) - Solano, Eduardo; Dendooven, Jolien; Minjauw, Matthias M.; Ramachandran, Ranjith K.; Van de Kerckhove, Kevin; Dobbelaere, Thomas; Hermida-Merino, Daniel; Detavernier, Christophe
Abstract : Correction for 'Key role of surface oxidation and reduction processes in the coarsening of Pt nanoparticles' by Eduardo Solano et al., Nanoscale, 2017, 9, 13159–13170.